2011
DOI: 10.1089/tmj.2011.0103
|View full text |Cite
|
Sign up to set email alerts
|

The Taxonomy of Telemedicine

Abstract: The purpose of this article is to present a taxonomy for telemedicine. The field has markedly grown, with an increasing number of applications, a variety of technologies, and newly introduced terminology. A taxonomy would serve to bring conceptual clarity to this burgeoning set of alternatives to in-person healthcare delivery. The article starts with a brief discussion of the importance of taxonomy as an information management strategy to improve knowledge sharing, facilitate research and policy initiatives, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
231
0
26

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(258 citation statements)
references
References 14 publications
1
231
0
26
Order By: Relevance
“…The components of the technological dimensions can be grouped into four variables: synchronicity, network design/configuration, connectivity and inter-operability [19].…”
Section: Equipment and Technologymentioning
confidence: 99%
“…The components of the technological dimensions can be grouped into four variables: synchronicity, network design/configuration, connectivity and inter-operability [19].…”
Section: Equipment and Technologymentioning
confidence: 99%
“…It has now emerged as a strategic approach or tool when designing maternal health research, programs and service delivery. 8 Health Information Systems (HIS) gather, aggregate, analyse and synthesize data from multiple sources to report on health; can include information related to patient records, disease surveillance, human resources, management of commodities, financial management, service delivery and other data needed for reporting and planning purposes.…”
Section: Formats Of Tm/thmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] They have concluded that mobile technology can be used to enhance the delivery of maternal health services by improving a client's knowledge and self-efficacy, a provider's competence, accountability and effectiveness; and, a health system's ability to manage its commodities, equipment and health workers.…”
Section: Research and Conceptualization Of M Healthmentioning
confidence: 99%
“…We adopt the approach of Bashshur et al, 5 who provide a clear and concise multidimensional taxonomy for telemedicine. This taxonomy does justice to the variety of telemedicine, and helps to identify the precise nature of a specific application.…”
Section: Telemedicine Taxonomymentioning
confidence: 99%
“…This taxonomy may help to better understand the implications for stakeholders in health care with regard to expansion of these innovative products for SL pathology. 5 We specifically focus on asynchronous telemedicine applications for dysarthria (ie, distorted speech production due to diminished force and coordination of speech muscles) 6 and aphasia (ie, distorted language understanding and production). …”
mentioning
confidence: 99%